An efficient stress and deformation model for arbitrary elastic-perfectly plastic adhesive lap joints. (December 2020) - Mardani, H.; Stein, N.; Rosendahl, P.L.; Becker, W.
Abstract: The present work introduces an efficient general sandwich-type model that allows for stress analyses of arbitrarily shaped adhesive lap joints with composite adherends with an elastic-perfectly plastic adhesive layer obeying the von Mises yield criterion. For the analysis of the nonlinear adhesive layer the plastic zone approach is applied. The model is applicable to various joint configurations, as e.g. single-lap joints, T-joints, L-joints, reinforcement patches or balanced double-lap joints. It considers only the overlap region of the joint with any combination of section forces and moments and is therefore denoted as sandwich-type model. First Order Shear Deformation Theory is employed to account for shear deformations of the composite adherends. Bending extension coupling is covered. The adhesive layer is assumed to be very thin compared to the thickness of the adherends and the shear and peel stress distributions are assumed as constant through the bondline thickness. To allow for a comparison of several different structural situations a two-dimensional Finite Element model of the overlap region is used. The stress distributions predicted by the present model are in good agreement with the results of detailed Finite Element analyses.